Enhancing Data Security Through VLSM Subnetting and TCP/IP Model in an ENT - Caxton Okoh; Waba Nasali Theophilus; Paul Dawkins; Sebamalai Paheerathan (Applied Sciences)
Data in-transit from an at-rest state can be securely transmitted and managed within a network. Background: This work covers the design and simulation of an Enhanced Network Topology (ENT) with multiple components that connects multiple locations of an imaginary organisation structure. The components of the network locations are mix-vendor components. The focus is on how classless IP address allocation, routing protocols, hierarchical network topology, and the updated Transmission Control Protocol/Internet Protocol (TCP/IP) model are put together to enhance performance and security. The simulation is performed using Cisco Packet Tracer where the packet transfer and connections within the network are examined. Methods: The Variable Length Subnet Mask (VLSM) approach is applied to a network design to secure data and information. We provided and detailed the implementation of subnetting, routing protocols, the updated TCP/IP model, and simulation within Cisco Packet Tracer. Our paper demonstrates the applicability of a single IP address range (0-255) where only the fourth octet changes to serve to secure information across networks through creating subnets. Results: The results of the simulation are further analysed; the security protocols are summarised. Conclusions: Our work has potential to be applied to Supervisory Control and Data Acquisition (SCADA) networks, Internet of Things (IoT) and Cloud networks; a useful resource for academia and industry professionals.